Newly developed Mg2+-selective fluorescent probe enables visualization of Mg2+ dynamics in mitochondria. - Yutaka Shindo (Public Library of Science (PLoS), 2011)
Mg(2+) plays important roles in numerous cellular functions. Mitochondria take part in intracellular Mg(2+) regulation and the Mg(2+) concentration in mitochondria affects the synthesis of ATP. However, there are few methods to observe Mg(2+) in mitochondria in intact cells. Here, we have developed a novel Mg(2+)-selective fluorescent probe, KMG-301, that is functional in mitochondria. This probe changes its fluorescence properties solely depending on the Mg(2+) concentration in mitochondria under physiologically normal conditions. Simultaneous measurements using this probe together with a probe for cytosolic Mg(2+), KMG-104, enabled us to compare the dynamics of Mg(2+) in the cytosol and in mitochondria. With this method, carbonyl cyanide p-(trifluoromethoxy) phenylhydrazone (FCCP)-induced Mg(2+) mobilization from mitochondria to the cytosol was visualized. Although a FCCP-induced decrease in the Mg(2+) concentration in mitochondria and an increase in the cytosol were observed both in differentiated PC12 cells and in hippocampal neurons, the time-courses of concentration changes varied with cell type. Moreover, the relationship between mitochondrial Mg(2+) and Parkinson's disease was analyzed in a cellular model of Parkinson's disease by using the 1-methyl-4-phenylpyridinium ion (MPP(+)). A gradual decrease in the Mg(2+) concentration in mitochondria was observed in response to MPP(+) in differentiated PC12 cells. These results indicate that KMG-301 is useful for investigating Mg(2+) dynamics in mitochondria. All animal procedures to obtain neurons from Wistar rats were approved by the ethical committee of Keio University (permit number is 09106-(1)).